A method for preparing an oxidation-resistant high-resistivity soft magnetic composite material
By mixing metal organic frames (Cu-MOFs) with nano-oxides and resins for insulating treatment, the problem of performance degradation of soft magnetic composite materials when improving oxidation resistance is solved, and the effects of high resistivity and low loss are achieved.
Patent Information
- Application Number
- CN202411890701.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The prior art is difficult to improve its oxidation resistance while ensuring the performance of soft magnetic composite materials. Traditional nano-oxide coating processes will sacrifice magnetic permeability and saturation magnetization, and the anti-rust treatment effect is limited.
Metal organic frames (Cu-MOFs) are mixed with nano-oxides and resins in a certain proportion, and insulating treatment is carried out to form a dense protective film, which improves the resistivity and oxidation resistance of soft magnetic powder.
It significantly reduces the loss of soft magnetic composite materials, effectively avoids oxidation, improves resistivity and oxidation resistance, and maintains excellent magnetic properties.
Smart Images

Figure CN119340056B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulation treatment of magnetic materials, and in particular relates to a method for preparing an oxidation-resistant high-resistivity soft magnetic composite material. Background Art
[0002] Soft magnetic composite materials are a kind of soft magnetic materials based on powder metallurgy process. They are widely used in many application fields due to their good magnetic properties. As power electronic devices continue to develop towards high frequency, high efficiency and high power, soft magnetic composite materials need to have higher resistivity, low high frequency loss and good magnetic permeability. In addition, some inductors working in special environments also need soft magnetic composite materials to have good anti-oxidation ability to prevent rust.
[0003] Although the traditional nano-oxide coating process can improve the resistivity of the soft magnetic powder core to a certain extent and reduce the eddy current loss under high frequency, it also sacrifices other properties of the soft magnetic powder core, such as magnetic permeability, saturation magnetization, etc. In addition, nano-oxides are prone to agglomeration during the coating process, resulting in uneven coating, which in turn causes the surface of the prepared soft magnetic composite material product to be easily oxidized. In order to avoid the occurrence of such rusting, the product needs to be additionally treated with rust prevention. For example, patent CN105097260A mentions a method for rust prevention of magnetic cores, which mainly achieves the anti-oxidation effect of the powder core by soaking the magnetic core in a water-based rust inhibitor. However, most of this water-based rust-proof oil only exists on the surface of the magnetic core after soaking. Once the powder core is bumped, rust is still inevitable. Patent CN112908605A takes into account the limitations of subsequent anti-rust measures and proposes a method for making a metal self-rust-proof magnetic powder core. The anti-rust work is advanced to the powder making process. The self-rust prevention of the magnetic powder core is achieved by doping with elements such as Cr and Ni. Although it has a certain anti-rust effect, the doping of other components during the smelting process will inevitably affect the magnetocrystalline anisotropy constant and magnetostriction coefficient, resulting in performance deterioration and noise problems.
[0004] Therefore, there is currently no effective solution to enable soft magnetic composite materials to have good antioxidant capabilities while ensuring that they have relatively excellent performance. Summary of the invention
[0005] In order to solve the problems existing in the existing methods for rust prevention of soft magnetic composite materials (including but not limited to the problems that water-based rust prevention oil cannot prevent rust completely, the high cost of the self-rust prevention process, the deterioration of performance, and the agglomeration of high-resistivity nano-oxides during the insulation process), the present invention discloses a method for preparing an oxidation-resistant high-resistivity soft magnetic composite material, by mixing antioxidant metal organic frameworks (Cu-MOFs) with nano-oxides and resin in a certain proportion, so as to achieve the insulation coating of iron-based alloy magnetic powder while also improving the resistivity and oxidation resistance of the soft magnetic powder.
[0006] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0007] A method for preparing an oxidation-resistant high-resistivity soft magnetic composite material comprises the following steps:
[0008] Step 1, adding the iron-based alloy powder into an acetone solution for ultrasonic cleaning and drying;
[0009] Step 2, mixing the metal organic framework Cu-MOFs powder, resin and nano oxide powder in a solvent to obtain a treatment liquid; adding the iron-based alloy powder treated in step 1 to the treatment liquid, stirring fully, standing, and drying to obtain an insulating iron-based alloy powder;
[0010] Step 3, uniformly mixing the mold release agent with the insulation-treated iron-based alloy powder, sieving, placing in a mold and pressing into shape to obtain a ring-shaped green body;
[0011] Step 4: Place the annular green body into a tubular furnace, and in a nitrogen atmosphere, first keep the temperature at 160-200° C. for 20-40 min, then heat it to 720-920° C., keep the temperature for 40-90 min, and air-cool it to obtain a soft magnetic composite material (i.e., an iron-based alloy powder core).
[0012] Furthermore, in step 1, the iron-based alloy powder is one of gas-atomized Iron-Silicon-Aluminum alloy powder, ball-milled Iron-Silicon-Aluminum alloy powder and gas-atomized Iron-Silicon alloy powder.
[0013] Furthermore, in step 1, the ultrasonic cleaning time is 5 to 10 minutes.
[0014] Furthermore, in step 2, the resin is one of phenolic resin, epoxy resin and silicone resin.
[0015] Furthermore, in step 2, the nano-oxide is a suspension of one of nano-silicon oxide, nano-aluminum oxide and nano-magnesium oxide.
[0016] Furthermore, in step 2, the amount ratio of the metal organic framework Cu-MOFs, resin, nano oxide and acetone in the treatment liquid is 0.5g:1g:3~8g:1L.
[0017] Furthermore, in step 2, the time for sufficient stirring is 10 to 20 minutes, the time for standing is 10 to 20 minutes, the temperature for drying is 60 to 100° C., and the time for drying is 30 to 60 minutes.
[0018] Furthermore, in step 3, the release agent accounts for 2-5‰ of the mass of the insulation-treated iron-based alloy powder.
[0019] Furthermore, in step 3, the pressing pressure is 1600-2100 MPa.
[0020] The oxidation-resistant high resistivity soft magnetic composite material prepared by the present invention has a relative magnetic permeability of 57-68 and a loss of 244-585 mW / cm at 50 kHz / 100 mT. 3 , the resistivity is 6.156×10 12 ~ 2.366×10 14 μΩ·cm.
[0021] The present invention innovatively uses metal organic frameworks (Cu-MOFs), taking advantage of the good compatibility of Cu-MOFs materials with resins and their good dispersion effect on nano-oxides, and the fact that Cu-MOFs materials themselves are excellent antioxidants, and applying their multifunctionality to the insulation coating process of soft magnetic composite materials, significantly reducing the loss of soft magnetic composite materials (including hysteresis loss and eddy current loss), and effectively avoiding the oxidation of soft magnetic powder core products. The beneficial technical effects of the present invention are specifically embodied in the following aspects:
[0022] 1. In addition to reducing the corrosion rate and inhibiting the oxidation of the metal matrix, the chain alkyl contained in the Cu-MOFs material gives Cu-MOFs hydrophobic properties, reducing the contact between the metal matrix and water. At the same time, the empty orbitals on atoms such as S and O in the Cu-MOFs molecules combine with the lone pairs of electrons on the surface of the magnetic powder to form bonds, so that Cu-MOFs are adsorbed on the surface of the magnetic powder particles to form a dense protective film, further enhancing the antioxidant effect.
[0023] 2. Cu-MOFs material has good compatibility with resin and is evenly dispersed in the coating system, effectively reducing the penetration path of the oxidizing medium. The rich functional groups of Cu-MOFs material can change the surface properties of nano-oxides, reduce the agglomeration effect of nano-oxides, and effectively improve the resistivity of the soft magnetic composite material after insulation treatment.
[0024] 3. Compared with samples prepared by conventional insulation processes, samples prepared by the process of the present invention have the advantages of high resistivity, low hysteresis loss and eddy current loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 For Comparative Example 1 ( Figure 1 (a)) and Example 1 ( Figure 1 (b) is a photograph of the appearance of the sample after 480 hours of salt spray test. DETAILED DESCRIPTION
[0026] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent claims of the present invention.
[0027] The particle size of the gas atomized iron-silicon alloy powder used in the following examples is 200 mesh.
[0028] The particle size of the metal organic framework Cu-MOFs powder used in the following examples is 500 nm.
[0029] In the following embodiments: relative magnetic permeability is measured by TH2816B LCR bridge, and the test condition is 100kHz / 1V. The test condition of loss is 50kHz / 100mT, and then the loss of 50kHz / 100mT test is separated to separate hysteresis loss and eddy current loss.
[0030] Example 1
[0031] The preparation method of the oxidation-resistant high-resistivity soft magnetic composite material provided in this embodiment has the following operating steps:
[0032] Step 1: Add the atomized iron-silicon alloy powder into an acetone solution and ultrasonically clean it for 5 minutes, then blow dry it with a hair dryer for later use.
[0033] Step 2: Evenly mix 0.5 g of metal organic framework Cu-MOFs powder, 1 g of phenolic resin and 3 g of nano silicon oxide powder in 1 L of acetone solution to obtain a treatment solution. Add 500 g of the atomized iron-silicon alloy powder treated in step 1 to the treatment solution, stir thoroughly for 10 min, let stand for 10 min, and dry at 60°C for 30 min to obtain an insulating iron-based alloy powder.
[0034] Step 3: Evenly mix 1g of the release agent with 500g of the iron-based alloy powder treated with insulation, pass through an 80-mesh sieve, put it into a mold and press it into shape at a molding pressure of 2100MPa to obtain a ring-shaped green body.
[0035] Step 4: Place the annular green body into a tubular furnace, anneal in a nitrogen atmosphere (first keep at 160°C for 20 minutes, then heat to 920°C and keep for 40 minutes), and air-cool the furnace to obtain a gas-atomized iron-silicon alloy magnetic powder core.
[0036] After testing, as shown in Table 1, the relative magnetic permeability of the aerosolized iron-silicon alloy magnetic powder core prepared in this embodiment is 61.7, and the loss at 50kHz / 100mT is 585mW / cm 3 , of which the hysteresis loss is 389mW / cm 3 , eddy current loss is 196mW / cm 3, the resistivity is 6.156×10 12 μΩ·cm.
[0037] Comparative Example 1
[0038] The preparation method of the soft magnetic composite material provided in this comparative example is the same as that of Example 1, except that the amount of Cu-MOFs powder added in step 2 is 0.
[0039] After testing, as shown in Table 1, the relative magnetic permeability of the aerosolized iron-silicon alloy magnetic powder core prepared in this comparative example is 62.6, and the loss at 50kHz / 100mT is 665mW / cm 3 , of which the hysteresis loss is 421mW / cm 3 , eddy current loss is 244mW / cm 3 , the resistivity is 8.623×10 9 μΩ·cm.
[0040]
[0041] From the performance comparison between Example 1 and Comparative Example 1, it can be seen that the resistivity of the sample obtained in the embodiment in which Cu-MOFs is added to the treatment liquid is significantly higher than that in the comparative example in which Cu-MOFs is not added, and the corresponding loss is also reduced. This is mainly because the increase in resistivity causes a decrease in eddy current loss, which leads to a decrease in total loss.
[0042] The atomized iron-silicon alloy magnetic powder cores prepared in Example 1 and Comparative Example 1 were subjected to a salt spray test: the spraying used a sodium chloride solution with a mass concentration of 5%, and the spraying temperature was controlled at 35°C; the conditions for wet heat storage were temperature (40±2)°C and relative humidity (93±3)%. Spraying and wet heat storage constituted one cycle, with a total of 20 cycles (480 hours). The results are shown in Figure 1 . Figure 1 (a) is a photograph of the appearance of the sample of Comparative Example 1 after 480 hours of salt spray test, and it can be seen that rust spots exist on the surface of the atomized iron silicon magnetic powder core. Figure 1 (b) is a photograph of the appearance of the sample of Example 1 after 480 hours of salt spray test. It can be seen that there is no rust on the surface of the aerosolized iron silicon magnetic powder core after Cu-MOFs treatment, showing a good anti-oxidation effect.
[0043] Example 2
[0044] The preparation method of the oxidation-resistant high-resistivity soft magnetic composite material provided in this embodiment has the following operating steps:
[0045] Step 1: Add the crushed Fe-Si-Al alloy powder into an acetone solution and ultrasonically clean it for 8 minutes, then blow dry it with a hair dryer for later use.
[0046] Step 2: Evenly mix 0.5 g of metal organic framework Cu-MOFs powder, 1 g of epoxy resin and 5 g of nano-alumina powder in 1 L of acetone solution to obtain a treatment solution. Add 500 g of the crushed iron-silicon-aluminum alloy powder treated in step 1 to the treatment solution, stir thoroughly for 15 min, let stand for 15 min, and dry at 80° C. for 45 min to obtain an insulating iron-based alloy powder.
[0047] Step 3: Evenly mix 1.75 g of a release agent with 500 g of an insulation-treated iron-based alloy powder, pass through an 80-mesh sieve, and place in a mold for compression molding at a molding pressure of 1850 MPa to obtain a ring-shaped green body.
[0048] Step 4: Place the annular green body into a tubular furnace, anneal in a nitrogen atmosphere (first keep at 180°C for 30 minutes, then heat to 820°C and keep for 60 minutes), air-cool with the furnace, and obtain a crushed FeSiAl alloy powder core.
[0049] After testing, the relative permeability of the crushed FeSiAl alloy magnetic powder core prepared in this embodiment is 68, and the loss at 50kHz / 100mT is 302mW / cm 3 , where the hysteresis loss is 223mW / cm 3 , eddy current loss is 79mW / cm 3 , the resistivity is 8.553×10 12 μΩ·cm.
[0050] Example 3
[0051] The preparation method of the oxidation-resistant high-resistivity soft magnetic composite material provided in this embodiment has the following operating steps:
[0052] Step 1: Add the atomized FeSiAl alloy powder into an acetone solution and perform ultrasonic cleaning for 10 minutes, then blow dry with a hair dryer for later use.
[0053] Step 2: Evenly mix 0.5 g of metal organic framework Cu-MOFs powder, 1 g of silicone resin and 8 g of nano magnesium oxide powder in 1 L of acetone solution to obtain a treatment solution. Add 500 g of the atomized iron-silicon-aluminum alloy powder treated in step 1 to the treatment solution, stir thoroughly for 20 min, let stand for 20 min, and dry at 100° C. for 60 min to obtain an insulating iron-based alloy powder.
[0054] Step 3: Evenly mix 2.5 g of a release agent with 500 g of an insulating iron-based alloy powder, pass through an 80-mesh sieve, and place the mixture into a mold for pressing at a molding pressure of 1600 MPa to obtain a ring-shaped green body.
[0055] Step 4, placing the annular green body into a tubular furnace, annealing in a nitrogen atmosphere (first keeping the temperature at 200°C for 40 minutes, then heating to 720°C and keeping the temperature for 90 minutes), air cooling with the furnace, and obtaining a gas atomized FeSiAl alloy magnetic powder core;
[0056] After testing, the relative magnetic permeability of the gas atomized Sendust aluminum alloy magnetic powder core of this embodiment is 57, and the loss at 50kHz / 100mT is 244mW / cm 3 , where the hysteresis loss is 189mW / cm 3 , eddy current loss is 55mW / cm 3 , the resistivity is 2.366×10 14 μΩ·cm.
[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any modification and equivalent changes made according to the method of the present invention still fall within the scope of protection of the present invention.
Claims
1. A method for preparing an oxidation-resistant high-resistivity soft magnetic composite material, characterized in that: The steps include: Step 1, adding the iron-based alloy powder into an acetone solution for ultrasonic cleaning and drying; Step 2, mixing metal organic framework Cu-MOFs powder, resin and nano oxide powder in acetone to obtain a treatment solution, wherein the amount ratio of metal organic framework Cu-MOFs, resin, nano oxide and acetone in the treatment solution is 0.5g:1g:3~8g:1L; adding the iron-based alloy powder treated in step 1 to the treatment solution, stirring fully, standing, and drying to obtain an insulating iron-based alloy powder; the resin is one of phenolic resin, epoxy resin and silicone resin; the nano oxide is one of nano silicon oxide, nano aluminum oxide and nano magnesium oxide; Step 3, uniformly mixing the mold release agent with the insulation-treated iron-based alloy powder, sieving, placing in a mold and pressing into shape to obtain a ring-shaped green body; Step 4: Place the annular green body into a tubular furnace, and in a nitrogen atmosphere, first heat it at 160-200°C for 20-40 minutes, then heat it to 720-920°C, heat it for 40-90 minutes, and air-cool it with the furnace to obtain a soft magnetic composite material; the relative magnetic permeability of the soft magnetic composite material is 57-68, and the loss at 50kHz / 100mT is 244-585mW / cm 3 , the resistivity is 6.156×10 12 ~ 2.366×10 14 μΩ·cm.
2. The method for preparing an oxidation-resistant high-resistivity soft magnetic composite material according to claim 1, characterized in that: In step 1, the iron-based alloy powder is one of ball-milled iron-silicon-aluminum alloy powder and gas-atomized iron-silicon alloy powder.
3. The method for preparing an oxidation-resistant high-resistivity soft magnetic composite material according to claim 1, characterized in that: In step 2, the time for sufficient stirring is 10 to 20 minutes, the time for standing is 10 to 20 minutes, the temperature for drying is 60 to 100° C., and the time for drying is 30 to 60 minutes.
4. The method for preparing an oxidation-resistant high-resistivity soft magnetic composite material according to claim 1, characterized in that: In step 3, the release agent accounts for 2-5‰ of the mass of the insulation-treated iron-based alloy powder.
5. The method for preparing an oxidation-resistant high-resistivity soft magnetic composite material according to claim 1, characterized in that: In step 3, the pressing pressure is 1600-2100 MPa.
6. An oxidation-resistant, high-resistivity, soft magnetic composite material obtained by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Rust protection method for magnetic core
CN105097260A
Metal self-rust-proof magnetic powder core and manufacturing method thereof
CN112908605A
Insulation method for improving oxidation resistance of metal magnetic powder core and material thereof
CN111192757A
MOFs material modified epoxy composite coating and preparation method thereof
CN115160893A